PERENCANAAN BANGUNAN KLINIK PASCA GEMPA CIANJUR (STUDI KASUS: KLINIK BIDAN KELURAHAN CIBULAKAN, KAB. CIANJUR) - Azaria Andreas; Irfan Ihsani; Resti Nur Arini; Fadli Kurnia; Ayu Herzanita (Program Studi Teknik Sipil Fakultas Teknik Universitas Pancasila, 2024)
The potential for earthquakes in Indonesia is caused by 2 conditions, namely, Indonesia's location which is located on the Pacific ring of fire, and Indonesia's location which is located at the meeting point of 3 active tectonic plates. The Cianjur earthquake in 2022 was a shallow crustal tectonic earthquake that occurred at a depth of around 10 km with a strength of 5.6 Mw. This main earthquake was followed by 140 aftershocks with strengths ranging from 1.2 to 4.2 Mw. Seeing the large potential for earthquakes in Indonesia, the Ministry of Public Works in 2006 issued guidelines for earthquake resistant building design. The earthquake also had an impact on the midwife clinic located in Cibulakan Urban Village. Where when an earthquake occurs, the building immediately collapses and is razed to the ground. Until 2024, the midwife clinic building will still not be erected and medical activities will be carried out in residential homes. Therefore, this research intends to carry out planning and construction of a 40 m2 building for medical activities. The design of the midwife clinic building takes the philosophy of earthquake-resistant houses built in earthquake-prone areas. One of the building concepts that must be applied in areas prone to earthquake disasters is building structural materials that are relatively lighter than materials in general, but still have sufficient strength. The results of the analysis show that building a midwife clinic costs Rp. 57,277,690 includes tax with a construction time of 32 calendar days.